Proceedings of the International Conference on Digital Technologies in Logistics and Infrastructure (ICDTLI 2019) 2019
DOI: 10.2991/icdtli-19.2019.61
|View full text |Cite
|
Sign up to set email alerts
|

Transport infrastructure safety improvement based on digital technology implementation

Abstract: The digital technology implementation in the transport infrastructure safety practice promotes reducing accident rates on Russian roads, however, the nationwide tasks of achieving "vision zero" have not been achieved yet. One of the tasks of improving the transport infrastructure safety is the implementation of systems for automatic traffic offence recording as the basis for a digital model in the field of transport infrastructure. For many years, Russia has been improving the state and business interaction me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…ere has been a dramatic shift in the way news is disseminated since the introduction of digital technologies and the subsequent advancement of computer, multimedia, communication, and network technologies. e digitization and networking of news dissemination have changed the existence of news dissemination, the transmission content, and the temporal and spatial relationship of human activities and will create a broader space for news dissemination [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…ere has been a dramatic shift in the way news is disseminated since the introduction of digital technologies and the subsequent advancement of computer, multimedia, communication, and network technologies. e digitization and networking of news dissemination have changed the existence of news dissemination, the transmission content, and the temporal and spatial relationship of human activities and will create a broader space for news dissemination [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to psychophysical and other human factors that affect road traffic safety, there are also external factors that shape transport safety and create conditions for the effective operation of police authorities and units, namely: introduction of innovative digital technologies, which are based on systems of automatic accounting of traffic offenses, digitization of transport infrastructure to ensure interaction between the subjects of automatic accounting of traffic offenses against the laws, implementation and operation of other systems (Marusin et al, 2019), geographical location, length of roads, and infrastructure. Recent world events caused by the Covid-19 pandemic have shown that an important factor influencing transport safety is a social one.…”
Section: Discussionmentioning
confidence: 99%
“…PTI is a framework that supports public transport (Marusin et al 2019). These are roads, pavements, bridges, public transport services that take place on them, stops and stations (Taylor 2021).…”
Section: Public Transport Infrastructurementioning
confidence: 99%
“…Efficient public transport is undoubtedly one of the leading indicators of a sustainable and resilient city (Mohmand et al 2021). Sustainable public transport is enshrined with an efficient infrastructure that enables access to economic activities, ensures safety and supports the national economy (Marusin et al 2019;Ogryzek et al 2020). Nevertheless, in most African cities, public transport is faced with enormous challenges emanating from a lack of sufficient infrastructure to support existing public transport (Helon & Ejem 2021).…”
Section: Introductionmentioning
confidence: 99%